2018
DOI: 10.1111/1365-2745.12986
|View full text |Cite
|
Sign up to set email alerts
|

Invaders among locals: Alien species decrease phylogenetic and functional diversity while increasing dissimilarity among native community members

Abstract: 1. Plant invasions can drastically change the structure of native communities, but it is not fully understood whether alien species occupy phylogenetic and functional space within the range occupied by natives, or provide a novel set of evolutionary origins and traits to the invaded communities.2. Here, we evaluated this open question with data on a large number of plant communities from different terrestrial habitats. We used ~27,000 vegetation plots from 26 terrestrial habitats in the Czech Republic and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
82
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(88 citation statements)
references
References 56 publications
5
82
0
1
Order By: Relevance
“…In addition, at the vegetation‐plot level, the exotic species with clustered phylogenetic fields tended to be phylogenetically closely related to their recipient native species (Figure ). This pattern is in line with previous findings in the Czech Republic, where exotic plant species more often occupied an existing phylogenetic space created by native species at the local community level (Loiola et al, ) and species pool level (Lososová et al, ). These findings indicated that exotic plant species that were closely related to native species were sorted into local assemblages that suggested the predominance of habitat filtering, even at a local scale, through phylogenetically conserved ecological niches (Chytrý et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, at the vegetation‐plot level, the exotic species with clustered phylogenetic fields tended to be phylogenetically closely related to their recipient native species (Figure ). This pattern is in line with previous findings in the Czech Republic, where exotic plant species more often occupied an existing phylogenetic space created by native species at the local community level (Loiola et al, ) and species pool level (Lososová et al, ). These findings indicated that exotic plant species that were closely related to native species were sorted into local assemblages that suggested the predominance of habitat filtering, even at a local scale, through phylogenetically conserved ecological niches (Chytrý et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…Observational studies frequently reported a positive association between the diversity of native communities and the likelihood of being invaded (e.g. Loiola et al, 2018;Stohlgren, Barnett, & Kartesz, 2003). However, with a few exceptions (Robinson & Dickerson, 1984), studies with experimentally constructed communities that tested for Elton's diversity-invasibility hypothesis often found evidence that diversity is a barrier to species invasions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, the ability to overcome biotic filters is best represented by similarity to the species present within the local community (Figure b). Such an approach can increase our understanding of the role of phylogenetic relatedness in invasion by identifying scale‐dependent relationships (e.g., within multiple community types in the Czech Republic; Lososová et al., ; Loiola et al., ); however, examples of closely and distantly related invaders being successful are common at both local and regional spatial scales according to a recent review (Cadotte et al., ). This suggests that phylogenetic relationships, on their own, may be unable to predict how invaders respond to either environmental or biotic filters.…”
mentioning
confidence: 99%